Key Steps and Characteristics for Successful Interdisciplinary Research: An Analytical Review - Vajaradul, Yongyuth; Aroonsrimorakot, Sayam; Laiphrakpam, Meena; Paisantanakij, Warit (The Journal of Behavioral Science, 2021)
There is an increasing importance of the application of interdisciplinary research (IDR) in all kinds of disciplines over the past two decades as it helps to improve a researcher’s career and also enables them to compete successfully in the job market. The term “interdisciplinary” means collaboration and integration of different disciplines with aims to find or develop something new. However, IDR has many challenges, in terms of integrating different theories of different disciplines. So, it is very important to study and follow the systematic steps and characteristics of IDR for successful integration. This article has been framed through literature review from various available sources and then categorized using content analysis method. The article aims to describe 1. definition and importance of IDR; 2. steps of IDR; and 3. characteristics of IDR approach. The article defined IDR as a collaboration or synthesis of two or more disciplines to develop a better methodology for conducting complex research problems, identified the main steps of IDR as team formation, identifying the research problem, selecting collaborators, and a strong team leader for effective team management. Among the important characteristics of IDR includes clarity of objectives, sharing, adaptability, team members’ willingness to cooperate, team leader and management, flexibility, improvement in communication strategies, dedication, cooperation, and clarity of objectives for successful integration or synthesis of IDR. This review is expected to be helpful to future researchers, who need to adopt IDR methodology for solving complex research problems.